Synthesis and Characterization of Human Body Trace Elements Substituted Hydroxyapatite for a Bioactive Material - Song, Shitao; Wu, Suxia; Lian, Qi; Peng, Youshun; Zheng, Xuefang; Zhang, Zhiwei (Asian Journal of Chemistry, 2013)
Zinc, manganese and ferrus substituted hydroxyapatite (HA) have been synthesized by sol-gel technique. The structure, morphology and biological activity of the synthetic samples were characterized by XRD, SEM and amino acid adsorption experiments. Comparative studies were carried out with hydroxyapatite, zinc substituted hydroxyapatite, manganese substituted hydroxyapatite and ferrum substituted hydroxyapatite. Manganese and ferrum substitution in hydroxyapatite reduced its crystallinity and particles size and increased the specific surface area of hydroxyapatite. Biological activity studies evidenced that the presence of zinc, manganese and ferrum in hydroxyapatite improved the biological activity of hydroxyapatite and Zn-hydroxyapatite showed better biological activity than the others. This study shows that the trace elements substituted hydroxyapatite have very good biocompatibility, which is an excellent bone substitution material.